Individuality and Diversity in Modular Education Process - Rajabboevna, Alimova Nozima (European Journal of Life Safety and Stability (2660-9630), 2022)
In the teaching process, the teacher expresses based on the requirements of technologyachieved learning objectives. The effectiveness of teaching in the accelerated period is mainly the learnerhis role in the teaching process depends on the attitude of the educator towards himwill be. Here we distinguish two types of teaching technologypossible: authoritarian and person-centered.